An Overview for Interaction of Boundary Layer with Advanced MHD Hypersonic Flow - Dr.P.Sree Divya, J.Madhavi (International Journal of Advanced Science and Technology, 2020)
A model for the analysis of the magneto plasma dynamic regime devoted to magneto hydrodynamics (MHD) systems in a hypersonic flight vehicle. In the paper, overview of interaction with boundary layer of MHD with hypersonic flow is presented. Here the flow of discrete formulation of fluid dynamics and electrodynamics are coupled. The electrodynamics is discrete by means of a finite-element method. The model has been utilized for the analysis of MHD interaction for the fluid control over a hypersonic body. This is mainly used in the application of advanced aerospace vehicles. Various types of geometric configurations are used which are basic in nature for the field of MHD fluid flow. Here the overview of cylindrical MHD fluid flow is studied which accelerates the facility of tunnel for interaction. The wedge models use hyper velocity in MHD fluid flow which ionizes the air flow with the parameters for interaction. Hence this interaction will provide effective output compared to other models.   Keywords: Magneto Hydro Dynamics (MHD), Space Vehicles, Hyper Sonic Flow, Wedge Models.